Pembuatan Jadwal Retensi Arsip pada Arsip Fasilitatif di Museum Musik Indonesia - Martinasashy Olivia Zoelkarnaen; Ellyn Eka Wahyu (INDO PUBLISHING, 2025)
This research is motivated by field findings showing that records management at MMI is not well-organized, particularly regarding facilitative records. This has led to difficulties in information retrieval, accumulation of records, and risk of data loss. The aim of this study is to create an Archive Retention Schedule (JRA) for facilitative records at MMI and to identify the challenges encountered in their management. The research method used was action research with a descriptive qualitative approach The scope of this study focuses on facilitative archives in the last five years, including financial, personnel, legal, public relations, secretarial, and governance documents. The data were collected by means of observation, interview and documentation. Finally, the data were analyzed qualitatively. The results of the study showed that the process of compiling a JRA involved several stages, namely the formation of a work team, archive inventory, drafting, and discussion to reach a final agreement. The preparation of the JRA provided guidance for museum staff in determining the storage period for active, inactive archives, and archives that were going to be destroyed or made permanent. This activity improved work efficiency, reduced the risk of losing important information, and ensured compliance with applicable archival regulations, as well as optimizing storage space. The conclusion of this research is that the records retention schedule plays a very important role in improving records management at MMI. It is useful in preserving important information, facilitating data retrieval, and serving as a reference for staff to effectioely manage records. It is recommended to conduct continuous training for all staffs and to carry out regular evaluations and updates of the records retention schedule every 2 to 5 years